Ease of EVs: Exploring factors that influence battery consumption. Issue 9 (1st July 2020) - Bartels, Rachel L.; Kowalsky, Daniel; Jonas, Tim; Macht, Gretchen A.
Abstract: Battery electric vehicles (BEVs) are becoming increasingly popular, showing annual sales growth, yet adoption is still limited. Maximizing distance driven between charges can improve user perceptions and usability of BEVs. Therefore, the ability to identify factors that influence a BEV's state of charge (SOC) in a naturalistic, experimental environment contribute to accomplishing transit sustainability. This study explores whether BEV drivers' use of five different energy regenerative braking modes, in conjunction with other potential influencing factors (e.g., trunk load), make a significant difference on the SOC. Using a randomized 3-factor factorial design, two drivers traveled the same path 20 times each, exceeding 160 miles each, for over 320 total miles of experimentation in a 2015 Volkswagen (VW) e-Golf. Significant differences were found between regenerative braking settings and the 3-way interactions between driver, load, and setting. Additional analysis suggests that only two regenerative braking settings (i.e., low regenerative braking and high regenerative braking) are actually required in addition to traditional braking, as the SOC does not change between all four regenerative braking settings. Furthermore, a posteriori, it was found that external temperature played a significant role in the SOC. Future research should focus on empirically detailing these differences between BEV drivers and SOC, validating and improving theoretically or simulation derived contexts. Ultimately, in an effort to transition society to a BEV future, this research seeks to harness patterns that affect a BEV's range, in order to maximize traveling distance between charges, to help reduce the threshold of user adoption.